PENGAMATAN PERILAKU TRANSIENT - Winarsih, Irda (Jurnal Teknik Elektro, 2002)
Observation on transient behavior is crucial because from this stuty we are able tocomprehend major parameters possessed by various electrical and electronic appliances.For this purpose of observation, appropriate measuring instruments/ equipments arenecessary. Sometimes it is difficult in realizing the expected observation. In many cases,transient behavior can improve the performance and efficiency of electrical devices; while insome other cases it may result in instability, or even failure in the system. By studying theresponses of RLC circuit, at least we can have some interpretation and explanation about thefundamental of transient bahavior in numerous electrical and electronic equipments. Thereare several parameters, which can be analyzed such as maximum voltage and time (peaktime tm and settling time ts), from the RLC circuits discussed in the next topic.Keywords: Transient, RLC circuits, peak time, settling time.